Elements of the nature and properties of soils - Brady, Nyle C. Weil, Ray R (Pearson Prentice Hall, 2010)
With an emphasis on the fundamentals, this book explores the important world of soils and the principles that can be used to minimize the degradation and destruction of one of our most important natural resources. Fully updated in this edition, it includes the latest information on soil colloids; nutrient cycles and soil fertility; and soils and chemical pollution. This edition is filled with hundreds of new